SREBP2 promotes the viability, proliferation, and migration and inhibits apoptosis in TGF-β1-induced airway smooth muscle cells by regulating TLR2/NF-κB/NFATc1/ABCA1 regulatory network. Issue 2 (1st February 2022) - Wang, Yuebin; Yang, Huike; Su, Xian; Cao, Anqiang; Chen, Feng; Chen, Peng; Yan, Fangtao; Hu, Huirong
ABSTRACT: Asthma is a respiratory disease with complex pathogenesis. Sterol-responsive element-binding proteins 2 (SREBP2) was found to bind to promoter sequences of ABCA1 to suppress ABCA1 promoter activity. This study aimed to explore the expression level of SREBP2 and ATP-binding cassette transporter A1 (ABCA1), and their effects on the development of airway smooth muscle cells (ASMCs) in asthma. ASMCs were treated with different concentrations of TGF-β1 (0, 0.5, 1, 5 and 10 ng/mL). Short hairpin SREBP2 (shSREBP2), SREBP2, shABCA1 or ABCA1 were transfected into ASMCs. Cell viability, proliferation, apoptosis, migration, and the expression of SREBP2, ABCA1 and related pathway proteins were detected by MTT assay, Brdu staining, flow cytometer, Transwell assay, qRT-PCR, and Western blotting, respectively. The results showed that TGF-β1 increased the viability, proliferation, migration and inhibited apoptosis in ASMCs. Moreover, TGF-β1 also decreased the expression of ABCA1, cleaved caspase-3, cleaved PARP, E-cadherin, and increased the expression of vimentin, TLR2, p-p65 and NFATc1. SREBP2 knockdown alleviated these TGF-β1-induced changes. SREBP2 overexpression inhibited ABCA1 expression and apoptosis, and promoted cell migration and the expression of TLR2, p-p65, NFATc1 in ASMCs. ABCA1 overexpression alleviated these SREBP2-induced promoting and inhibition effects. In conclusion, SREBP2 activates TLR2/NF-κB/NFATc1 regulatory network and promotes TGF-β1-induced cell movement through inhibiting ABCA1 expression. GRAPHIC ABSTRACT: uf0001